THU0079 The Association between Patient Reported Outcomes and Clinical Examination in Newly Diagnosed Spondyloarthritis Patients: Results from the Be-Giant Cohort. (10th June 2014) - Varkas, G.; Cypers, H.; Van Praet, L.; Carron, P.; Raeman, F.; Gyselbrecht, L.; Devinck, M.; Corluy, L.; Vanneuville, B.; Elewaut, D.; Van den Bosch, F.
Abstract : Background: The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) is a well-known surrogate for the patient's perception of disease activity, and is frequently used as an inclusion criteria for clinical trials. The BelGian Inflammatory Arthritis and spoNdylitis cohorT (Be-Giant) is a new multicentre, observational cohort in which patients with non-radiographic-axial Spondyloarthritis (nr-axSpA) and peripheral SpA, classified according to the ASAS criteria, are prospectively followed every six months. Objectives: To assess the association between patient reported outcomes and clinical examination. Methods: Currently 123 newly diagnosed early SpA patients have been included. The present study describes the link between the three BASDAI questions covering physical discomfort of SpA patients and their relationship with the clinical examination as defined by swollen joint count (SJC) and modified Maastricht Ankylosing Spondylitis Enthesitis Score (MASES), including evaluation of the plantar fascia. These questions include the overall level of AS neck, back or hip pain (question 2 (Q2)); the overall level of pain/swelling in joints other than neck, back or hips (Q3) and the overall level of discomfort from any areas tender to touch/pressure (Q4). Concerning peripheral joint involvement, we defined the following groups: no swollen joints, oligoarticular (1-3 SJC) and polyarticular disease (>3 SJC). Concerning enthesitis-scores, we distinguished between involvement of the heel entheses and the more axial located entheses of the MASES. Results: In our cohort we found that patients presenting with swollen joints scored significantly higher with regard to BASDAI Q3, than patients without swollen joints (P<0.0001). Patients with oligo- or polyarticular disease also showed significantly higher ASDAS values compared to patients without synovitis (respectively P=0.001 and P=0.015). There was no significant difference between oligo- and polyarticular joint disease concerning global BASDAI, ASDAS or the individual BASDAI Q3. BASDAI Q4 was not influenced by the presence of axial enthesitis; nor was the global BASDAI or ASDAS. However, presence of heel enthesitis did result in significant higher values for BASDAI Q4 (P<0.0001), global BASDAI (P=0.002), but not ASDAS. When evaluating BASDAI Q2 we found significantly higher values in the presence of axial enthesitis. Conclusions: In our early SpA cohort we found an association between patient reported outcomes and clinical examination. We found that BASDAI question 3 regarding pain or swelling of the joints does capture the presence of synovitis, but could not differentiate between oligo- and polyarticular disease. BASDAI question 4 about tender points seems to signal heel enthesitis rather than axial enthesitis. Axial enthesitis, in its turn, seems to be reported as neck, back or hip pain (BASDAI question 2). In conclusion, the different components of the BASDAI are a good reflection of the clinical examination. To our knowledge this is the first study to validate the link between patient-reported outcomes and the evaluation of the physician. Acknowledgements: The Be-Giant cohort is funded by an unrestricted grant by AbbVie. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4995